Peripheral territories: Imagining common worlds differently - Engels- Schwarzpaul, A.-Chr. (Interstices: Journal of Architecture and Related Arts, 2020)
At the beginning of spatial struggle is separation: perception of what is in, or outside of, one’s body, one’s house, kin, neighbourhood, and polity. We all have vague or even detailed ideas of that separation—but this we often goes unnoticed, the very notion that performs the very separation we imagine. For instance, we tend to associate a territory with a nation-state and a homogenous population, while a periphery appears to lack connection and substance. Marking territory along these associations is challenging after forty years of global neoliberal politics, resulting in the displacement of millions of people and austere biopolitical measures. Against this backdrop, this paper explores the politics of place and mobility, exemplified by two case studies, one in the Mediterranean and the other in the Pacific, to raise an urgent contemporary question: how can we negotiate between the freedom of movement, on the one hand, and the protection of Indigenous land rights and self-determination, on the other?